Re-validation and re-description of an endemic and threatened species, Aphanius pluristriatus (Jenkins, 1910) (Teleostei, Cyprinodontidae), from southern Iran - Esmaeili, Hamid Reza; Teimori, Azad; Gholami, Zeinab; Zarei, Neda; Reichenbacher, Bettina (Zootaxa, 2012)
Aphanius pluristriatus (Jenkins, 1910) (Cyprinodontidae) is a poorly known species from Fasa, located in the Mond Riverdrainage system, east of Shiraz, southern Iran. It has not been investigated since its first description, its validity has beenquestioned and a synonymy with A. sophiae (Heckel, 1849) has been suggested. In this study, we describe a new collectionof Aphanius specimens from the Zarjan spring system, which is probably the same spring system from where Jenkins(1910) collected the type specimens of A. pluristriatus. The morphological characters of our new series of specimens areconsistent with those of A. pluristriatus as originally described by Jenkins (1910). We emend the original description ofA. pluristriatus and add morphometric and meristic data. A comparison with the related taxa A. sophiae, A. farsicus (for-mer A. persicus) and A. isfahanensis reveals that A. pluristriatus can be separated from them by a smaller caudal peduncleindex, higher number of flank bars, lower number of gill rakers, and higher J scale index. Therefore A. pluristriatus rep-resents a valid species, which is at present restricted to the drainage system of the Mond River. We suggest that A. pluris-triatus originated from an ancient A. sophiae population in the Kor River Basin during the Quaternary. At that time, theKor River was draining to the Persian Gulf by the “Paleo-Kor River” and the Mond River. During the Late Quaternary orHolocene, the connection between the Kor River and the Persian Gulf has been blocked as a result of tectonic uplift (theKor River Basin is endorheic today). Thus, A. pluristriatus most likely is the relict of an ancient Aphanius population from the Quaternary “Paleo-Kor River” drainage system.